PENGEMBANGAN MODEL BELAJAR KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SEKOLAH DASAR - Hadli, Hadli; Ismi Mori Saputra, Deka (Program Studi Pendidikan Vokasi Seni Kuliner, 2026)
This article discusses the development of a cooperative learning model to improve the learning outcomes of sixth grade elementary school students. Developing a Cooperative Learning Model to Improve Learning Outcomes for Class VI Elementary School Students is a classroom action research that aims to improve student learning outcomes through the application of cooperative learning models. This research was conducted on 18 sixth grade elementary school students using the classroom action research method. The research results show that the application of the cooperative learning model can significantly improve student learning outcomes, increase learning motivation, and strengthen social interactions. This model is also effective in developing students' critical thinking skills, creativity and communication skills. Therefore, the cooperative learning model can be used as an alternative in the learning process to improve the quality of education.